Review articleSubstance P and its receptors – a potential target for novel medicines in malignant brain tumour therapies (mini-review) - Łazarczyk, Marzena; Matyja, Ewa; Lipkowski, Andrzej (Folia Neuropathologica, 2007)
Tachykinins are excitatory neuropeptides synthesised in neuronal and glial cells of the human central and peripheral nervous system. They participate in both physiological and certain pathological conditions, i.e. synaptic transmission, nociception and neuroimmunomodulation. Tachykinins act as excitatory neurotransmitters and/or neuromodulators and induce DNA synthesis leading to stimulation of cell division and proliferation. Their biological responses are triggered via the well-established tachykinin receptors NK1, NK2 and NK3 that belong to the G protein-coupled receptor family (GPCRs). Substance P is the most important member of the tachykinin family that constitutes the major endogenous ligand for the NK1 receptor type. The presence of functional NK1 receptors has been documented in malignant brain tumours of glial origin. It has been evidenced that SP-NK1 receptor communication is involved in glioma development and progression. It is possible because the tumour cells display SP-mediated autocrine activity, the ability of cytokines stimulation and MAP kinases activation. It has been suggested that SP receptor antagonists application might be useful in attempts directed at anti-cancer therapy.